Temporomandibular disorders and cervical dysfunctions in hospital workers - Limaylla Cecilio, Rubén (2008)
Several investigations explain that under physiologic conditions the cervical rachis influences the Temporo Mandibular Junction dynamics; being deduced that in pathological situation, pathology of Tempano Mandibular Junction would take place. According to this concept many authors determine that patients with Temporo Mandibular Disorders (TMD) show a higher prevalence of cervical dysfunctions, while others disagree this point. The investigation tries to clarify this alternative; being carried out a study of traverse and descriptive type; being selected 51 subjects of the staff of the department dentistry of the Hospital Military Central. Being used the index of Krogh Poulsen to evaluate the presence of TTD and the technique of Penning; to evaluate the alterations of the cervical posture; the data were processed through the test of CHI squared (x2). Being a prevalence of 50.9% of TTD and 75.5% of prevalence of abnormal cervical posture. The frequency of abnormal cervical posture in subjects with TTD was of 73.1%; while in the subjects without TTD with it was of 56%. not being significant to the test of Chi squared.